2008
DOI: 10.1097/mpa.0b013e3180d0a738
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Identification in Human Pancreatic Cancer Sera

Abstract: The fact that inflammation-sensitive proteins were identified as increased in pancreatic cancer sera supports the hypothesis that inflammatory-driven processes are involved in pancreatic carcinogenesis. Liquid ESI-MS analyses of sera hold promise for future pancreatic cancer blood tests as well as for understanding mechanisms of pancreatic carcinogenesis. The variability observed between the low-mass regions of normal versus pancreatic cancer spectra may aid in diagnosis and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…ApoE is non-covalently bound to A2M in human plasma, and therefore, the present in silico analysis of ApoE binding may provide insights into the pathogenic and intracellular role of ApoE in cancer cells. In addition, A2M has previously been reported as a candidate biomarker for the early diagnosis in numerous types of cancers, including gastric cancer (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…ApoE is non-covalently bound to A2M in human plasma, and therefore, the present in silico analysis of ApoE binding may provide insights into the pathogenic and intracellular role of ApoE in cancer cells. In addition, A2M has previously been reported as a candidate biomarker for the early diagnosis in numerous types of cancers, including gastric cancer (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30] Hanas et al reported that complement C3 was elevated in the serum of patients with pancreas cancer. 31 Lee et al found that complement C3a was elevated in the serum of patients with hepatitis C-related hepatocellular carcinoma. 32 In addition, Bjorgem et al…”
Section: Discussionmentioning
confidence: 99%
“…S4). In addition, 17 of these proteins have been previously shown to be up-regulated in pancreatic cancer in at least four studies (61), and 10 have been shown to be elevated in pancreatic cancer serum in comparison to controls (60,(63)(64)(65)(66)(67)(68)(69)(70)(71) (Table III). The unstudied proteins might yield promising new candidate biomarkers for pancreatic cancer.…”
Section: Differential Expression Of Proteins In Cancer Versus Normalmentioning
confidence: 99%